A subjective descriptive study of the warm‐up and turn to a fence, approach, take‐off, suspension, landing and move‐off in 10 showjumpers. (19th December 2016) - Dyson, S.; Tranquille, C.; Walker, V.; Guire, R.; Fisher, M.; Murray, R.
Summary: There is limited knowledge about causes of musculoskeletal injury in showjumpers. The objectives were to describe features of the turn, approach and jump in a group of experienced showjumpers believed by their riders to be sound, to relate these findings to clinical findings, and to identify features that may predispose to injury. Ten experienced showjumpers in normal competition training jumped an upright and a parallel fence four times off the left and right reins respectively, after a rider‐defined period of warm‐up. Real‐time and high‐speed motion capture was undertaken. Detailed subjective assessment of the gait was performed during the warm‐up, on the turn and approach to the jump and all phases of the jump. Six horses had thoracolumbar pain or epaxial muscle tension. Six horses exhibited a poor‐quality canter. The mean duration of warm‐up was 7 min (range 5–10 min). All horses had lean of the trunk and hindlimbs >45° on the turn. The inside hindlimb was placed in front of the outside hindlimb in 75% of the turns. Sideways oscillations of the hocks during stance were seen in all horses on the turn and on the straight approach in five horses. The inside hindlimb had greater magnitude of oscillation than the outside hindlimb on the turns. Repeated asynchronous push‐off with the hindlimbs at take‐off was seen in three horses. The hindlimbs drifted to the left or right during the ascent‐phase of suspension in four horses, reflecting asymmetrical push‐off. Only two horses landed consistently with the correct forelimb leading relative to the direction in which the horse had to turn after the fence. Four horses landed seven (n = 2) or eight (n = 2) times each with the left (n = 2) and right (n = 2) forelimbs respectively. Repetitive overload through asymmetrical use of the left and right canter leads, inadequate warm‐up, and limb instability could potentially predispose to injury.